Critical empathy through oral histories after apartheid. Issue 5 (3rd September 2017) - Field, Sean
Abstract: Through a critique of empathy based on a 'sharing of feelings' or 'identifications' in search of rapport, this article rather frames 'critical empathy' as a discursive strategy to approach oral history dialogues and interpretation. Through interpretations of oral histories with survivors of apartheid violence, I argue that empathy for oral historians involves imagining past scenes through the positions and perspectives of the speaking other. However, these empathic imaginings must be bounded by critical analysis, self-reflexivity and working through the intersubjective production of alterity in fieldwork dialogues. Critical empathy is neither in search of reconciliation nor equality. These political ideals are not preconditions for open dialogues. But oral historians need to do more work on how survivors work to translate – in psychic and cultural terms – their stories through the dissonance between how they see themselves and how researchers recognize or misrecognize them through the alterity of 'inter-views'. In South Africa, critical empathy forged through the alterity of racialized dissonance facilitates interviewee's imaginings of the 'death of relationships' to people, places and dreams, which echoes the 'afterwardsness' of colonialism and apartheid.